Multifunctional PLA/Gelatin Bionanocomposites for Tailored Drug Delivery Systems - Carmen Moya-Lopez; Alberto Juan; Murillo Donizeti; Jesus Valcarcel; José A. Vazquez; Eduardo Solano; David Chapron; Patrice Bourson; Ivan Bravo; Carlos Alonso-Moreno; Pilar Clemente-Casares; Carlos Gracia-Fernández; et al. (MDPI AG, 2022)
A series of bionanocomposites composed of shark gelatin hydrogels and PLA nanoparticles featuring different nanostructures were designed to generate multifunctional drug delivery systems with tailored release rates required for personalized treatment approaches. The global conception of the systems was considered from the desired customization of the drug release while featuring the viscoelastic properties needed for their ease of storage and posterior local administration as well as their biocompatibility and cell growth capability for the successful administration at the biomolecular level. The hydrogel matrix offers the support to develop a direct thermal method to convert the typical kinetic trapped nanostructures afforded by the formulation method whilst avoiding the detrimental nanoparticle agglomeration that diminishes their therapeutic effect. The nanoparticles generated were successfully formulated with two different antitumoral compounds (doxorubicin and dasatinib) possessing different structures to prove the loading versatility of the drug delivery system. The bionanocomposites were characterized by several techniques (SEM, DLS, RAMAN, DSC, SAXS/WAXS and rheology) as well as their reversible sol-gel transition upon thermal treatment that occurs during the drug delivery system preparation and the thermal annealing step. In addition, the local applicability of the drug delivery system was assessed by the so-called "syringe test" to validate both the storage capability and its flow properties at simulated physiological conditions. Finally, the drug release profiles of the doxorubicin from both the PLA nanoparticles or the bionanocomposites were analyzed and correlated to the nanostructure of the drug delivery system.